Fundamentals of programming languages - Chancellor, Chris (New York : Larsen and Keller Education, 2022)
"Fundamentals of Programming Languages" by Chris Chancellor offers a comprehensive exploration of the essential concepts and principles underlying programming languages. The book covers a wide range of topics, from basic syntax and semantics to more advanced subjects like static typing and standard libraries. It provides a valuable resource for both beginners and experienced programmers, offering insights into the development processes and future trends in the field of programming languages. Whether you're interested in understanding the building blocks of programming or exploring the latest advancements, this textbook provides a solid foundation.
Includes index.
Keywords: Programming languages; Language design and implementation; Programming Language Paradigms